Aesthetics Of Wayang Symbols On The Ceiling Of Graha Sahid Surakarta Building: Cultural Influence In Interior Design - Dina Kristiana Seftianingsih; Rafia, Indy; Dian Muhammad Rifai; Dea Syahnas Paradita (Universitas Veteran Bangun Nusantara Sukoharjo, 2024)
This research explores the use of wayang symbols in the ceiling design of Graha Sahid Surakarta and its impact on cultural aesthetics in interior design. Wayang as a traditional Indonesian art has symbols with deep cultural and philosophical meanings. The purpose of this study is to analyze how wayang symbols are applied in ceiling design to create a balance between cultural heritage and modern architecture. The research methodology uses qualitative which includes literature study, observation and interviews with building designers and building users. The findings of this study show that the application of wayang symbols on the ceiling of Graha Sahid Surakarta not only enhances the aesthetic value but also strengthens the cultural identity of the building. The integration of wayang motifs in the ceiling design shows how cultural elements can be combined with contemporary aesthetics to produce a unique and meaningful space. This research highlights the importance of understanding and applying cultural symbols in interior design to enrich the experience of space and strengthen cultural connections in a modern context.